Pengembangan media e-learning berbasis web untuk mendukung kemampuan pemecahan masalah siswa SMP pada materi aljabar - Nuryami; Hanifa (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
This study aims to develop web-based learning media in the form of e-learning on the topic of algebra to improve junior high school students' problem solving ability. This research uses a mixed method with the ADDIE development approach as well as an experiment with a pretest-posttest control group design. The research was conducted at MTs involving 20 students as samples. The results of the validation show that this learning media is valid, with a validation score from media experts of 92% and from material experts of 88%. The field test showed that the average student response was 71.7%, which was categorized as “good”. N-gain analysis showed an increase in students' ability to solve problems with an average score of 0.6724, indicating significant effectiveness. This research implies that web-based learning media can be an innovative solution to overcome challenges in learning mathematics in junior high school, especially on algebra topics that are often considered difficult. This media is able to motivate students, improve understanding, and provide flexible and interactive learning alternatives. However, further research is needed with a larger sample size to ensure the results can be generalized